2006
DOI: 10.1159/000092870
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Regulating the Ductus Arteriosus

Abstract: A patent ductus arteriosus (PDA) results in increased pulmonary blood flow and redistribution of flow to other organs. Several co-morbidities (i.e., necrotizing enterocolitis, intracranial hemorrhage, pulmonary edema/hemorrhage, bronchopulmonary dysplasia, and retinopathy) are associated with the presence of a PDA, but whether or not a PDA is responsible for their development is still unclear. In this review, comparative physiology between the full term and preterm newborn and the barriers preventing the neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
199
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(208 citation statements)
references
References 99 publications
3
199
1
5
Order By: Relevance
“…With our present results we can only speculate about the functional consequences of the low relaxant potency of PGE2 in the chicken DA. In the mammalian fetus, circulating concentrations of PGE2 appear to be of placental origin (Clyman 2006). To the best of our knowledge, there is no study in the literature examining prostanoids levels in avian embryos or the role of the choriallantoic membrane, the analogous of mammalian placenta, in the production of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With our present results we can only speculate about the functional consequences of the low relaxant potency of PGE2 in the chicken DA. In the mammalian fetus, circulating concentrations of PGE2 appear to be of placental origin (Clyman 2006). To the best of our knowledge, there is no study in the literature examining prostanoids levels in avian embryos or the role of the choriallantoic membrane, the analogous of mammalian placenta, in the production of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 plays a major role in prenatal patency and postnatal closure of the mammalian DA, namely during fetal life by exerting a potent relaxant eVect (Clyman 2006;Smith 1998), possibly in conjunction with nitric oxide (NO, Coceani et al 1994;Momma and Toyono 1999;Seidner et al 2001;Takizawa et al 2000), and after birth by abruptly withdrawing its action. We have previously shown that the transition to ex ovo life is accompanied by dramatic changes in chicken DA reactivity (Agren et al 2007(Agren et al , 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, both the absence and the reversal of renal arterial flow in infants with a HSDA have been demonstrated. 5,38 Although clinical evidence of renal dysfunction/failure is apparent in these patients, 2 causality has not been ascribed, even though normalization of renal arterial Doppler after ductal closure is temporally associated with clinical improvement. PDA is usually characterized by low diastolic blood pressure and diastolic run off through the ductus toward the lower pulmonary vascular resistance circuit.…”
Section: Clinical Relevance Of Ductal Stealmentioning
confidence: 99%
“…2 A HSDA has been previously defined by a transductal diameter >1.5 mm with echocardiographic findings of a significant transductal shunt (for example, left atria:aorta ratio >1.4, unrestrictive transductal flow on pulse-wave Doppler with velocity <1.5 m per s). 3 This may be accompanied by clinical features of pulmonary overcirculation (for example, increased oxygen or ventilation requirements) and/or systemic hypoperfusion (for example, hypotension and metabolic acidosis).…”
Section: Introductionmentioning
confidence: 99%